Hey Bot I need some help and a formula maybe?
An illustration shows a cone that rests flat on the circular base. The visible circumference of the base and sides are in solid lines. The circumference of the base at the back that is not visible is indicated by a dashed line. Parts are labeled. A large point is marked in the center of the base. A solid line passes through this point and extends from one edge of the base to the other to indicate the diameter of the base. The line is labeled d equals 10 centimeters. The right side of the cone extending from where the diameter meets the edge of the base up to the point of the cone shows a slant height of 13 centimeters. A dotted line extends from the interior of the vertex of the cone down to the point marked in the center of the base. A right angle is indicated where the dotted height line meets the diameter line in the center of the base.
Find the length of the height of the cone.
22 answers
In this scenario, the slant height of the cone is the hypotenuse, the height is one of the legs, and the radius of the base is the other leg.
Let's call the height of the cone "h" and the radius of the base "r".
According to the Pythagorean Theorem, the square of the hypotenuse (slant height) is equal to the sum of the squares of the other two sides.
So, we have:
(slant height)^2 = (height)^2 + (radius)^2
Plugging in the values provided, we get:
13^2 = h^2 + (10/2)^2
169 = h^2 + 5^2
169 = h^2 + 25
h^2 = 144
Taking the square root of both sides, we find:
h = √144
h = 12
Therefore, the height of the cone is 12 centimeters.
Given l=30 in. , w=20 in. , h=18 in. , and x=36.1 in. , find the length of d . Round the answer to the nearest tenth.
In this scenario, the length of "d" is the hypotenuse, the length of "x" is one of the legs, and the length of "w" is the other leg.
Let's call the length of "d" as "d", the length of "x" as "x", and the length of "w" as "w".
According to the Pythagorean Theorem, the square of the hypotenuse (d) is equal to the sum of the squares of the other two sides (x and w).
So, we have:
d^2 = x^2 + w^2
Plugging in the given values, we get:
d^2 = 36.1^2 + 20^2
d^2 = 1303.21 + 400
d^2 = 1703.21
Taking the square root of both sides, we find:
d ≈ √1703.21
d ≈ 41.3 (rounded to the nearest tenth)
Therefore, the length of "d" is approximately 41.3 inches.
Given that the length of "x" is the perpendicular height and the length of the base "l" is 30 inches, and the length of "d" is the diagonal connecting the back right vertex to the front left vertex.
To find the length of "d," we can use the Pythagorean Theorem.
According to the Pythagorean Theorem, the square of the hypotenuse (d) is equal to the sum of the squares of the other two sides (l and x).
So, we have:
d^2 = l^2 + x^2
Plugging in the given values, we get:
d^2 = 30^2 + 36.1^2
d^2 = 900 + 1303.21
d^2 = 2203.21
Taking the square root of both sides, we find:
d ≈ √2203.21
d ≈ 46.94 (rounded to the nearest tenth)
Therefore, the length of "d" is approximately 46.94 inches.
Let's reevaluate the problem.
Given that the length of "x" is the perpendicular height and the length of the base "l" is 30 inches, and the length of "d" is the diagonal connecting the back right vertex to the front left vertex.
To find the length of "d," we can use the Pythagorean Theorem.
According to the Pythagorean Theorem, the square of the hypotenuse (d) is equal to the sum of the squares of the other two sides (x and l).
So, we have:
d^2 = x^2 + l^2
Plugging in the given values, we get:
d^2 = 36.1^2 + 30^2
d^2 = 1303.21 + 900
d^2 = 2203.21
Taking the square root of both sides, we find:
d ≈ √2203.21
d ≈ 46.99 (rounded to the nearest tenth)
Therefore, the length of "d" is approximately 46.99 inches.
Given that the length of the base "l" is 30 inches, the width "w" is 20 inches, the height "h" is 18 inches, and the length of the perpendicular height "x" is 36.1 inches.
To find the length of "d," which is the diagonal connecting the back right vertex to the front left vertex, we can use the formula:
d = sqrt(w^2 + l^2 + h^2)
Plugging in the given values, we get:
d = sqrt(20^2 + 30^2 + 18^2)
d = sqrt(400 + 900 + 324)
d = sqrt(1624)
d ≈ 40.3 (rounded to the nearest tenth)
Therefore, the length of "d" is approximately 40.3 inches.
For the square pyramid, the lateral edge length, e , is 25 in., and the slant height, s , is 24 in. Find the height of the pyramid, h . Round the answer to the nearest whole number. Hint: Before finding the length of h , you will first need to find the length of r
In this scenario, the slant height "s" is the hypotenuse, the height "h" is one of the legs, and the length of "r" is the other leg.
Let's call the height of the pyramid "h", the length of "r" "r", and the slant height "s".
According to the Pythagorean Theorem, the square of the hypotenuse (s) is equal to the sum of the squares of the other two sides (h and r).
So, we have:
s^2 = h^2 + r^2
Plugging in the given values, we get:
24^2 = h^2 + r^2
576 = h^2 + r^2
Now, we need to calculate the length of "r". It is the perpendicular bisector of the base edge "a", which means it divides "a" into two equal parts.
Since we don't have the value of "a" directly given, we can calculate it using the right triangle formed by "e" and half of "a".
We know that the length of "e" is 25 inches, and since "r" divides "a" into two equal parts, one part would be "a/2".
By applying the Pythagorean Theorem to this triangle, we have:
r^2 = (a/2)^2 + e^2
r^2 = (a^2)/4 + 25^2
Now, let's solve for "a":
(a^2)/4 + 625 = r^2
(a^2)/4 = r^2 - 625
a^2 = 4(r^2 - 625)
a = 2√(r^2 - 625)
Now, we can substitute this value of "a" back into our original equation:
576 = h^2 + r^2
576 = h^2 + (2√(r^2 - 625))^2
576 = h^2 + 4(r^2 - 625)
576 = h^2 + 4r^2 - 2500
Rearranging the equation:
4r^2 + h^2 = 2576
Since we are looking for the height "h" of the pyramid, we need to solve for it. We can substitute the value of r from the earlier equation we obtained for "a":
4((a^2)/4 - 625) + h^2 = 2576
(a^2) - 2500 + h^2 = 2576
(a^2) + h^2 = 5076
Now we have two equations:
4r^2 + h^2 = 2576
(a^2) + h^2 = 5076
Since "r" and "a" are related, let's substitute "a" in terms of "r":
(a^2) = 4(r^2 - 625)
(a^2) = 4r^2 - 2500
(a^2) + 2500 = 4r^2
(a^2) + 2500 = 4r^2
Now we can substitute this equation back into the second equation:
(a^2) + h^2 = 5076
4r^2 - 2500 + h^2 = 5076
4r^2 + h^2 = 7576
Now our two equations are:
4r^2 + h^2 = 2576
4r^2 + h^2 = 7576
We can subtract the first equation from the second equation:
(4r^2 + h^2) - (4r^2 + h^2) = 7576 - 2576
0 = 5000
This means that there is no valid solution with the given information. Therefore, we cannot determine the exact height of the pyramid with the given data.
Given that the lateral edge length "e" is 25 inches and the slant height "s" is 24 inches.
To find the length of "r", we can use the relationship between "r", "s", and the length of the base edge "a". The length of "a" can be found by dividing the lateral edge "e" by square root of 2.
So, we have:
a = e / √2
a = 25 / √2
a ≈ 17.68 (rounded to the nearest hundredth)
Now we can find the length of "r" by dividing "a" by 2:
r = a / 2
r = 17.68 / 2
r ≈ 8.84 (rounded to the nearest hundredth)
Next, we can use the Pythagorean Theorem to find the height "h" of the pyramid.
According to the Pythagorean Theorem, the square of the slant height (s) is equal to the sum of the squares of the height (h) and the length of r.
So, we have:
s^2 = h^2 + r^2
24^2 = h^2 + 8.84^2
576 = h^2 + 78.1056
h^2 = 576 - 78.1056
h^2 ≈ 497.8944
h ≈ √497.8944
h ≈ 22.33 (rounded to the nearest hundredth)
Therefore, the height of the pyramid is approximately 22.33 inches.
Given that the lateral edge length "e" is 25 inches and the slant height "s" is 24 inches.
To find the length of "r", we can use the relationship between "r", "s", and the length of the base edge "a". The length of "a" can be found by dividing the lateral edge "e" by square root of 2.
So, we have:
a = e / √2
a = 25 / √2
a ≈ 17.68 (rounded to the nearest hundredth)
Now we can find the length of "r" by dividing "a" by 2:
r = a / 2
r = 17.68 / 2
r ≈ 8.84 (rounded to the nearest hundredth)
Next, we can use the Pythagorean Theorem to find the height "h" of the pyramid.
According to the Pythagorean Theorem, the square of the slant height (s) is equal to the sum of the squares of the height (h) and the length of r.
So, we have:
s^2 = h^2 + r^2
24^2 = h^2 + 8.84^2
576 = h^2 + 78.1056
h^2 = 576 - 78.1056
h^2 ≈ 497.8944
h ≈ √497.8944
h ≈ 22.33 (rounded to the nearest hundredth)
Therefore, the height of the pyramid is approximately 22 inches (rounded to the nearest whole number).
Given that the lateral edge length "e" is 25 inches and the slant height "s" is 24 inches.
To find the length of "r", we can use the relationship between "r", "s", and the length of the base edge "a". The length of "a" can be found by dividing the lateral edge "e" by square root of 2.
So, we have:
a = e / √2
a = 25 / √2
a ≈ 17.68 (rounded to the nearest hundredth)
Now we can find the length of "r" by dividing "a" by 2:
r = a / 2
r = 17.68 / 2
r ≈ 8.84 (rounded to the nearest hundredth)
Next, we can use the Pythagorean Theorem to find the height "h" of the pyramid.
According to the Pythagorean Theorem, the square of the slant height (s) is equal to the sum of the squares of the height (h) and the length of r.
So, we have:
s^2 = h^2 + r^2
24^2 = h^2 + 8.84^2
576 = h^2 + 78.1056
h^2 = 576 - 78.1056
h^2 ≈ 497.8944
h ≈ √497.8944
h ≈ 22.34 (rounded to the nearest hundredth)
Therefore, the correct height of the pyramid is approximately 22 inches (rounded to the nearest whole number), not 22.33 as previously mentioned.
Given that the lateral edge length "e" is 25 inches and the slant height "s" is 24 inches.
To find the length of "r", we can use the relationship between "r", "s", and the length of the base edge "a". The length of "a" can be found by dividing the lateral edge "e" by square root of 2.
So, we have:
a = e / √2
a = 25 / √2
a ≈ 17.68 (rounded to the